2015
DOI: 10.1248/bpb.b15-00444
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilatory Effect of Wogonin on the Rat Aorta and Its Mechanism Study

Abstract: 1) These compounds might contribute to the anti-hypertensive effect collectively. However, the anti-hypertensive effect of Eucommia ulmoides OLIV. bark remains largely unclear.Pharmacological studies have revealed that Eucommia ulmoides OLIV. bark extract induce endothelium and NO-cyclic guanosine monophosphate (cGMP) dependent relaxation in the rat thoracic aorta.2) Another report demonstrated that the endothelium-dependent vascular relaxation induced by the bark extract is mediated by NO and endothelium-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The association with NO in GCs raised the possibility that wogonin suppresses GCs by increasing the NO release. However, in our study, L-NAME did not affect the wogonin-induced reduction of GCs, which is consistent with a previous report in the aorta (14). Furthermore, a soluble guanylyl cyclase inhibitor, ODQ, also did not affect the inhibitory action of wogonin on GCs.…”
Section: Discussionsupporting
confidence: 92%
“…The association with NO in GCs raised the possibility that wogonin suppresses GCs by increasing the NO release. However, in our study, L-NAME did not affect the wogonin-induced reduction of GCs, which is consistent with a previous report in the aorta (14). Furthermore, a soluble guanylyl cyclase inhibitor, ODQ, also did not affect the inhibitory action of wogonin on GCs.…”
Section: Discussionsupporting
confidence: 92%
“…It was recommended that kaempferol is a naturally occurring compound that has inhibitory and stimulatory function on ER stress (Ashrafizadeh et al, 2020). Qu et al (2015) reported that wogonin prevented the increase of Ca 2+ initiated by KCl (60 mm) after exhausting calcium stored in sarcoplasmic and endoplasmic reticula with thapsigargin (1 μm) or by ATP (100 μm) in VSMCs. Wogonin is a flavone and has a mixture of cardiovascular defensive effects.…”
Section: Cardioprotectionmentioning
confidence: 99%
“…This finding indicates that wogonin protects neurons by promoting microvascular formation and subsequently restoring blood supply via the TGF- β 1 pathway. The vasodilatory effect of wogonin mediated by inhibition of both intracellular Ca 2+ release and extracellular Ca 2+ influx could be a potential treatment paradigm for ischemia [ 121 ]. This evidence strongly supports the feasibility of developing baicalein, baicalein, and wogonin as candidates for neuroprotection following ischemic stroke.…”
Section: Neuroprotective Effects Of Baicalein Baicalin and Wogonin On The Brain And Retina Ischemiamentioning
confidence: 99%
“…Through modulating the MAPK pathway and the production of apoptotic factors, these flavonoids effectively rescue neurons in the brain and retina [ 100 , 112 , 113 , 115 , 123 , 127 , 128 , 131 ]. In addition, the blockage of ion channel dysfunction after ischemic stress remarkably ameliorates the excitotoxicity caused by ion overload and subsequently decreases neuronal death [ 86 , 121 ]. Taken together, all the evidence strongly supports the feasibility of developing these flavonoids as natural neuroprotectants.…”
Section: Pathways Targeted By Baicalein Baicalin and Wogonin During Neuroprotective Processesmentioning
confidence: 99%